Strengthening Participatory Governance through Post-Harvest Sports Activities: Experiences of Public Administration Students in Facilitating Village Policy Discussions in Maccope Village - Muslimin Muslimin (Universitas Cahaya Prima, 2025)
This community service program aimed to strengthen community participation in village policy formulation through the integration of traditional post-harvest sports activities (Malanca) and participatory discussions facilitated by Public Administration students participating in the Community Service Program (KKN) in Maccope Village. The program employed a participatory and collaborative approach involving local residents, village authorities, students, and other stakeholders in planning, implementation, and evaluation processes. Data were collected through observation, participatory discussions, interviews, and documentation. The findings revealed that the establishment of the Maccope Mandiri Group significantly enhanced citizens’ involvement in village planning and budgeting processes. Capacity-building activities improved residents’ understanding of APBDes mechanisms and strengthened their ability to formulate and advocate policy proposals. Traditional Malanca sports functioned not only as cultural and recreational activities but also as informal arenas for policy deliberation and civic education. Multi-stakeholder collaboration fostered communication between villagers and local authorities, resulting in increased transparency and accountability. Although infrastructural limitations and unequal access to information remained challenges, the program demonstrated that integrating local culture with participatory governance can promote community empowerment and democratic practices. The experience of Maccope Village provides an alternative model for strengthening policy literacy, preserving cultural heritage, and encouraging sustainable community participation in rural development